Fixed drug eruption – A retrospective review of 146 patients in a tertiary hospital in Southern Taiwan - Jui-Wen Yeh; Wei-Ting Liu (Dermatologica Sinica)
In this retrospective study, the clinical characteristics of 146 patients diagnosed with fixed drug eruption (FDE) in a tertiary hospital in Southern Taiwan were analyzed. The median age of subjects was 62 years, with a predominance of males (63.7%). Pediatric cases comprised only 5.5% of the series, while 53.4% were nonelderly adults. The results indicate a median interval of 1.5 days between drug intake and skin eruption, with 22% of patients requiring hospitalization. Bullous formations were noted in 78.8% of cases, and mucosal involvement was present in 47.3%, primarily affecting the lip, oral and genital mucosa. Among the 61 patients with documented causative agents, nonsteroidal anti-inflammatory drugs (NSAIDs) were the most common (37.7%), followed by antibiotics (31.1%). Three mortality cases were reported, all complicated with underlying illness, and two of which were generalized bullous fixed drug eruption (GBFDE) cases. We also conducted statistical analyses between the GBFDE and non-GBFDE groups, as well as a comparison of clinical presentations among different categories of culprit drugs. The study emphasizes the repeated nature of FDE, the severity of GBFDE, and the need for increased awareness of NSAIDs as common triggers. Overall, these findings contribute insights into the characteristics and management of FDE, reflecting a critical need for improved patient care strategies.